Contemporary english (McGraw-Hill, 2005)
Contemporary English second edition has refined the content and skills adult ESL students need to know to survive and thrive living in the United States. The emphasis on grammar, vocabulary, graphic literacy, critical thinking skills, life skills, and workplace skills has all been retained and presented in meaningful contexts through topics of high interest to adult students. Lessons are self-contained, remaining appropriate for both standard and open enrollment situations.. .